Socialization of Basketball Game Rules - I Putu Agus Dharma Hita; Komang Ayu Krisna Dewi; I Ketut Addy Putra Indrawan; Elsa Ariestika; Doni Pranata (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
The community service activity entitled "Socialization of Basketball Game Regulations" was held at Dauhwaru basketball court, Jembrana District, Bali Province on January 5, 2023. The activity was attended by 47 participants and aimed to improve participants' knowledge of basketball regulations. Prior to the material presentation, participants were given a pre-test, followed by a post-test after the material was given. The results of this activity showed an improvement in scores between the pre-test and the post-test. It is important to provide clear understanding and explanation of basketball game rules to players, especially beginners. In addition, the socialization of basketball game rules needs to be conducted continuously and involve coaches and referees to provide a deeper understanding of the rules. The socialization activity of basketball game rules is very effective in improving participants' knowledge and understanding of game regulations and can provide a fun experience for participants.